2003
DOI: 10.1111/j.1474-8673.2003.00298.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological characterization of α2‐adrenoceptor‐mediated responses in pig nasal mucosa

Abstract: 1. Pig nasal mucosal strips were incubated with alpha-adrenoceptor antagonists followed by alpha2-adrenoceptor agonist concentration-response curves. 2. Contractions elicited by the alpha2-adrenoceptor agonists BHT-920 (pD2 = 6.16 +/- 0.07), UK 14,304 (pD2 = 6.89 +/- 0.13) and PGE-6201204 (pD2 = 7.12 +/- 0.21) were blocked by the alpha2-adrenoceptor antagonist yohimbine (0.1 microm). In contrast, the alpha1-adrenoceptor antagonist prazosin (0.03 microm) had no effect on the BHT-920-, UK 14,304- and PGE-6201204… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 45 publications
1
24
1
3
Order By: Relevance
“…Indeed, nasal decongestion is triggered by an active constriction of the venous sinusoids (Kristiansen et al, 1993), and a decrease in nasal cavity pressure after ␣-adrenoceptor agonist administration reflects shrinkage of nasal capacitance vessels (Berridge and Roach, 1986). Several other studies in different species (Lacroix, 1989;Corboz et al, 2003Corboz et al, , 2007Corboz et al, , 2008Wang and Lung, 2003), including human (Johannssen et al, 1997;Corboz et al, 2005), indicated a predominance of the ␣ 2 -adrenenoceptor mechanism in the regulation of capacitance vessels. In addition, ␣ 2 -adrenoceptor proteins are expressed in human nasal mucosa (Corboz et al, 2005) and levels of ␣ 2 -adrenoceptor protein are higher than ␣ 1 -adrenoceptor protein in nasal mucosa of nonallergic and allergic patients (van Megen et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, nasal decongestion is triggered by an active constriction of the venous sinusoids (Kristiansen et al, 1993), and a decrease in nasal cavity pressure after ␣-adrenoceptor agonist administration reflects shrinkage of nasal capacitance vessels (Berridge and Roach, 1986). Several other studies in different species (Lacroix, 1989;Corboz et al, 2003Corboz et al, , 2007Corboz et al, , 2008Wang and Lung, 2003), including human (Johannssen et al, 1997;Corboz et al, 2005), indicated a predominance of the ␣ 2 -adrenenoceptor mechanism in the regulation of capacitance vessels. In addition, ␣ 2 -adrenoceptor proteins are expressed in human nasal mucosa (Corboz et al, 2005) and levels of ␣ 2 -adrenoceptor protein are higher than ␣ 1 -adrenoceptor protein in nasal mucosa of nonallergic and allergic patients (van Megen et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…This last observation confirms and extends those of previous pharmacological studies. Indeed, we reported previously that the ␣ 2C -adrenoceptor subtype is preferentially found in pig nasal mucosa (Corboz et al, 2003), whereas Stafford-Smith et al (2007) demonstrated by in situ hybridization that the ␣ 2C -adrenoceptor mRNA is the only ␣-adrenoceptor mRNA present in human nasal venous sinusoids and arteriovenous anastomoses. Although these pig models (organ chamber and real-time tissue contractility assays) have limitations with regard to translation of results to human, it is worthy of note that pig and human share several similarities such as the anatomy, morphology, physiology, histology, and biochemistry (Hare, 1975;Pound and Houpt, 1978;Corboz et al, 2007) Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Nasal vessels include arteries and arterioles (resistance vessels), arteriovenous connections, subepithelial and periglandular capillary networks which drain into collecting veins and venous sinusoids (capacitance vessels), and finally the sphenopalatine vein. 15,16 Initially investigating αAR effects on vascular tone, Ichimura et al 17 demonstrated the presence of postsynaptic α 1 ARs as well as pre-and postsynaptic α 2 ARs in canine nasal vascular smooth muscles using pharmacologic approaches. These findings suggested that stimulation of either α 1 or α 2 ARs would be expected to provide vascular smooth muscle contraction.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in humans suggest the primary mechanism underlying nasal decongestion appears to be venous constriction of the collecting veins and sinusoids; 15,16,[20][21][22][23] such constriction decreases engorgement of nasal mucosa, attenuating alterations in nasal anatomy that have been shown to alter nasal Presence of silver granules in cells resulting from in situ hybridization of αAR subtype mRNA probes scored by two independent observers. αAR = alpha-adrenergic receptor.…”
Section: Discussionmentioning
confidence: 99%
“…25,[31][32][33][34] Compounds in cluster C (spiroxatrine 9 and WAY 100635 10 (CCS >0.826)) again have similar functional activity profiles: they are antagonists for R 1 and serotonin 5HT1A receptors. [23][24][25][26][27] Cluster D with the next highest similarity score (CCS > 0.82) contains dopamine 21, N-methyldopamine 22, and 6,7-ADTN 23. These three compounds are full agonists both at dopamine and at adrenergic receptors.…”
Section: Relationship Between Biospectra Similarity and Functional Acmentioning
confidence: 99%